The antecedents of halal Malaysia brand equity based on consumers tolerance on product cue attributes - Wan Ismail, Wan Rusni; Othman, Mohhidin; Abdul Rahman, Russly; Kamarulzaman, Nitty Hirawaty; Ab Rahman, Suhaimi (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Previous studies on Halal logo only evolved around consumer’s decision making without considering and addressing what is the actual contribution of such logo instead of its influence in consumer’s decision making. To date, none of the studies sees beyond the Halal stamp as a logo itself. Nevertheless, the Halal logo is representing the only Halal assurance system in Malaysia; hence it should also be recognized as an important brand representing Malaysia. However, there are issues and implications when a logo is view as a brand because all brands carry underlying commercial value or equity which requires constant maintenance because record shows that even strong brands could still plunge into a deep pit. All brands will experience the fluctuation of brand value or equity at some pointof their life span,however there is no study that looks into the actual value of Halal Malaysia brand (HMB) yet. The fluctuation should be expected for a brand that does not offer any tangible productsuch as HMB and as Halal assurance system main functions are only to ensure that the product that carrying its mark really deliver their claim. The real challenge faced by HMB is when dealing with various products and producers that come with various reputations and track records. Besides, how significant the presence of HMB on familiar and intolerance product with ambiguous semiotics cue are still unknown and require further investigation. Thus the importance of HMB presence in any situation will point out its real value. Findings from the qualitative study will be used to develop instrument for a second stage of a quantitative study. This research is expected to yield results on whether the brand equity is consistent toward different product and consumers. Thus, the result from this study will contribute to a new body of knowledge on the Halal brand studies using a new model of Halal brand equity and consumer decision making.